A Sustainable Fluorescent SCDs-MPs Probe for Dopamine Insight Recognition in Human Fluids with Cytotoxicity Evaluation - Komal Murugan; Abirami Natarajan (Chemistry and Biochemistry: Research Progress Vol. 4, 2025)
This research presents a novel sensing platform for detecting dopamine, a crucial neurotransmitter, in biological fluids. The platform combines a signal-transducing element with a selective recognition component to achieve highly sensitive and specific dopamine detection. The sensing mechanism relies on the interaction between the target analyte (Dopamine) and the platform, resulting in a detectable change in signal. The developed sensor demonstrates a low detection limit and excellent recovery in complex biological matrices. Furthermore, biocompatibility assessments confirm the platform’s suitability for potential biological applications. This approach offers a promising tool for diagnosing neurological disorders and advancing our understanding of dopamine-related processes.